Reliability of thick Al wire: a study of the effects of wire bonding parameters on thermal cycling degradation rate using non-destructive methods - Arjmand, E.; Agyakwa, P.A.; Johnson, C.M. (Elsevier, 2014)
The effect of bonding parameters on the reliability of thick Al wire bond is investigated. Samples were prepared with 25 different designs with 5 different bonding parameters such as time, ultrasonic power, begin- force, end-force and touch-down steps (pre-compression) with 5 levels. The bond signals of ultrasonic generator were collected during bonding in order to obtain prior quality information of bonded wires. 3D x-ray tomography was then used to evaluate bond quality during passive thermal cycling between -55 °C and 125 °C. Tomography datasets were obtained from the as-bonded condition and during cycling. The results clearly show ultrasonic power, appropriate levels of begin-force and touch-down steps are all important for achieving a well attached and reliable bond. Analysis of the virtual cross-sections indicates a good correlation between the bond signal (i.e. the initial bond quality) and wire bond damage/ degradation rate. An improved understanding of the wire bonding process was achieved by observing the effect of the complex interaction of bonding parameters on the ultrasonic generator signals and degradation rate under thermal cycling.